Goal-Scoring Patterns in Elite Asian Youth Football: Evidence from the AFC U-17 and U-20 Asian Cups 2025 - Wisnu Arda Gutawa; Gigih Siantoro; Achmad Widodo; Irmantara Subagio; Himawan Wismanadi; Heri Wahyudi (INSPIREE: Indonesian Sport Innovation Review, 2026)
The  purpose  of  the study. This study aimed to analyze the contribution of set plays and open play to goal-scoring outcomes in elite Asian youth football by examining goal-scoring patterns in the AFC U-17 Asian Cup 2025 and AFC U-20 Asian Cup 2025, with particular attention to differences across age categories within the AFC youth competition context. Materials and methods. A descriptive observational research design was employed using systematic notational analysis. All goals scored in the AFC U-17 Asian Cup 2025 (n = 101) and the AFC U-20 Asian Cup 2025 (n = 93), resulting in a total of 194 goals, were included in the analysis. Each goal was classified based on the phase of play preceding the scoring action (open play or set play) and further categorized according to the final attacking action leading to the goal. Data were analyzed using descriptive statistics, including frequencies and percentages, to identify dominant goal-scoring patterns across tournaments and age groups. Results. The findings indicated that open play was the primary source of goals, accounting for 73.71% of total goals scored across both tournaments, while set plays contributed 26.29%. In the AFC U-17 Asian Cup 2025, penalties constituted the highest proportion of set-play goals, whereas in the AFC U-20 Asian Cup, corner kicks were the most frequent set-play source. Analysis of open-play goals revealed that crosses and forward passes were the most common attacking actions leading to goals in both tournaments. A more balanced distribution of attacking actions was observed at the U-20 level, suggesting greater tactical variability compared to the U-17 competition. Conclusions. Open play represents the dominant mechanism of goal production in elite Asian youth football. Nevertheless, set plays remain a significant contributor to goal scoring, particularly at the U-17 level. The observed differences between age categories highlight age-related variations in tactical execution and goal-scoring patterns within AFC youth competitions, underscoring the importance of age-specific training and tactical preparation.